26 GHz phase shifters for multi-beam nolen matrix towards fifth generation (5G) technology - Norhudah Seman; Nazleen Syahira Mohd Suhaimi; Tien Han Chua (Bulletin of Electrical Engineering and Informatics, 2019)
This paper presents the designs of phase shifters for multi-beam Nolen matrix towards the fifth generation (5G) technology at 26 GHz. The low-cost, lightweight and compact size 0° and 45° loaded stubs and chamfered 90°, 135° and 180° Schiffman phase shifters are proposed at 26 GHz. An edge at a corner of the 50 Ω microstrip line Schiffman phase shifter is chamfered to reduce the excess capacitance and unwanted reflection. However, the Schiffman phase shifter topology is not relevant to be applied for the phase shifter less than 45° as it needs very small arc bending at 26 GHz. The stubs are loaded to the phase shifter in order to obtain electrical lengths, which are less than 45°. The proposed phase shifters provide return loss better than 10 dB, insertion loss of -0.97 dB and phase difference imbalance of ± 4.04° between 25.75GHz and 26.25 GHz. The Rogers RT/duroid 5880 substrate with dielectric constant of 2.2 and substrate thickness of 0.254 mm is implemented in the designs.